Pre-operative Exposure to Ustekinumab: A Risk Factor for Postoperative Complications in Crohn's Disease (CD)? - Shim, Hang H.; Ma, Christopher; Kotze, Paulo Gustavo; Panaccione, Remo (Current Drug Targets, 2019)
Crohn’s disease (CD) is a chronic inflammatory condition of the intestinal tract that is characterised by a relapsing and remitting course. Despite advancements in therapeutic options for CD, a substantial number of patients still require surgery for medically refractory disease or disease-related complications. Given the widespread adoption of biologic therapies for the management of patients with moderate-to-severe CD, a high number of patients are likely to be on biologic therapy at the time of needing intestinal surgery: the safety of biologics in perioperative setting is of great interest. While more clinical data are available for TNF antagonists and vedolizumab, the safety data for ustekinumab, an IL 12/23 inhibitor, is lacking. Here, we review the available data from published literature on the postoperative outcomes for CD patients exposed to ustekinumab perioperatively.
Keywords: chronic inflammatory